Incumbent responses to lower cost entry: Evidence from the US airline industry - Harumi Ito; Darin Lee (Brown University, Department of Economics, 2003)
This paper analyzes the responses of incumbent hub-and-spoke carriers to low cost carrier (LCC) entry on routes served to and from their hubs over the past decade. Our analysis finds that the typical price and capacity response by incumbent hub-and-spoke carriers to LCC entry has been fairly accommodating. Moreover, our analysis also finds-somewhat surprisingly-that the likelihood of an LCC's entry into a hub market being successful is unrelated to the relative response of the incumbent. – Airlines ; Entry ; Exit ; Accommodation ; Predation
Keywords: L11; L93; 330; Hub-and-Spoke-Netzwerk; Luftverkehr; Markteintritt; USA